Johannes Buridans Kategorienlehre - Wojtczak, Hanna (Folia Philosophica, 2018)
Jean Buridan was one of initiators of a new interpretation of Aristotle’s Categories. According to this interpretation, the subject matter of Aristotle’s work are significative terms in the function of subject and predicate and not the things meant or substitutive by these terms. In this way Buridan rejected some traditional belief that modi praedicanti are directly related to modi essendi. In consequence, he questioned the realist explanation of both number and variety of categories (ex parte rerum). At the same time, rejecting the idea of reduction of the differences between categories to the verbal level only, he finally stated that the source of the difference are various forms of predication of the first substance which are derived from various connotations of the terms. Buridan has set a canon for the way of commenting Categories for many years, and although the next generation of commentators shorten his list of questions, few basic ones were always included, namely those concerning the scope of each category, relation between them, their independence and some of their characteristics.